Investigating collector and depressant performance in the flotation of selected iron ores - Mhonde, Ngoni Pepukai (Centre for Minerals Research, 2017)
As the excessive extraction of high grade iron ore reserves has led to the rapid depletion of these ore bodies, there is a growing need to extract and upgrade low grade iron ores into more economically viable products with an iron content in excess of 50%. The beneficiation of low grade iron ores through the reverse cationic flotation procedure is gradually gaining popularity as a possible processing route of the future for South Africa's iron industry. Reverse cationic flotation employs a reagent suite consisting of an amine compound which functions as a quartz collector in addition to providing the frothing effect in the flotation system, and hydrolysed starch which serves to depress hematite during flotation. The aim of this project was to investigate the effect of using five amine collectors with different molecular structures on the flotation recovery of quartz and the entrainment of hematite in the flotation of a South African iron ore and a Brazilian iron ore. Laboratory batch flotation tests were conducted on both ore samples and the grade and recovery of hematite were recorded. The collectors were characterised through surface tension measurements and pKa value analysis. An attempt at using different polysaccharides as hematite depressants entailed the use of a CMC and a guar gum in batch flotation tests of the Brazilian iron ore.